Address Resolution Protocol Functions in The Ethernet - Harjono Harjono (JUITA : Jurnal Informatika, 2017)
Ethernet is the most popular network technology today. All devices connected within the network must follow protocols in order to communicate. One of the protocols in the TCP/IP protocol suites is the Address Resolution Protocol (ARP). The function of ARP is to translate logical addresses into physical addresses. This research aims to simulate the role of ARP in the Ethernet using Packet Tracer. The address resolution process performed by ARP, which originaly took place very quickly and was not visible. It can be observed in detail and clearly by the simulation. In the simulation, communication betwen hosts in the network can be done if the physical address of the destination host is known. If the physical address is not known then ARP will perform its function.